2014
DOI: 10.1371/journal.pone.0091646
|View full text |Cite|
|
Sign up to set email alerts
|

New miRNA Profiles Accurately Distinguish Renal Cell Carcinomas and Upper Tract Urothelial Carcinomas from the Normal Kidney

Abstract: BackgroundUpper tract urothelial carcinomas (UT-UC) can invade the pelvicalyceal system making differential diagnosis of the various histologically distinct renal cell carcinoma (RCC) subtypes and UT-UC, difficult. Correct diagnosis is critical for determining appropriate surgery and post-surgical treatments. We aimed to identify microRNA (miRNA) signatures that can accurately distinguish the most prevalent RCC subtypes and UT-UC form the normal kidney.Methods and FindingsmiRNA profiling was performed on FFPE … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
34
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(41 citation statements)
references
References 48 publications
6
34
0
Order By: Relevance
“…The miR-204-3p has been found to be deregulated in several tumors, such as hepatocellular carcinoma, glioma, and breast cancer (40)(41)(42), and is closely related with ccRCC and upper tract urothelial carcinomas (43). In our study, we found that circATP2B1 functions as the reservoir of miR-204-3p, by stabilizing or promoting the transcription of miR-204-3p to inhibit ccRCC invasion.…”
Section: Discussionsupporting
confidence: 54%
“…The miR-204-3p has been found to be deregulated in several tumors, such as hepatocellular carcinoma, glioma, and breast cancer (40)(41)(42), and is closely related with ccRCC and upper tract urothelial carcinomas (43). In our study, we found that circATP2B1 functions as the reservoir of miR-204-3p, by stabilizing or promoting the transcription of miR-204-3p to inhibit ccRCC invasion.…”
Section: Discussionsupporting
confidence: 54%
“…Moreover, as a transcriptional factor, p53 mainly exert its function through transcription regulation of its target genes to initiate various cellular responses. Furthermore, recent studies have demonstrated that miRNAs interact with p53 and its network at multiple levels …”
Section: Discussionmentioning
confidence: 99%
“…In the past 10 years, screens of miRNA expression in RCC have shown widespread miRNA dysregulation [179][180][181] . Of note, more mi RNAs were downregulated or silenced in renal tumours than in normal tissue, and this downregulation or silencing [Au: OK?]…”
Section: Bap1mentioning
confidence: 99%